2010
DOI: 10.3109/09546630902991484
|View full text |Cite
|
Sign up to set email alerts
|

A case of imiquimod-induced alopecia

Abstract: Imiquimod cream 5% is an immune modifier approved for the treatment of genital warts, actinic keratosis, and basal cell carcinoma. This case report presents an isolated case of telogen effluvium after 6 weeks of imiquimod treatment for an actinic keratosis on the scalp. Based on this case presentation, telogen effluvium is a potential rare side effect from imiquimod treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The most common of those weird systemic side effects are influenza-like symptoms and headache. A review of the literature revealed lots of unusual adverse reactions related to the topical use of this drug, which are summarized in table 1[10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common of those weird systemic side effects are influenza-like symptoms and headache. A review of the literature revealed lots of unusual adverse reactions related to the topical use of this drug, which are summarized in table 1[10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57]. …”
Section: Discussionmentioning
confidence: 99%
“…epidermoid cysts, alopecia or chronic neuropathic pain [23,45,57]. However, to our knowledge, acute renal failure caused by imiquimod in immunologically impaired patients has not been described in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the FIP could be considered as a nontoxic, safety-acceptable and biocompatible adjuvant . 38,39 Also, IMQ just dissolve in acid solution, then further stimulate the body and has some safety risk. An effective solution to the problem is covalent ligation of IMQ to a larger carrier, which prevent them uncontrolled systemic distribution.…”
Section: Figure 3 the Fi-ir Images Of Fip And Related Substrates Cellular Cytotoxicitymentioning
confidence: 99%
“…Figure 4. The cell viability of each sample with differentconcentration Pure IMQ has been reported to cause many adverse reactions, such as local skin inflammation, erosion and ulcer when injected skin 38,39. Also, IMQ just dissolve in acid solution, then further stimulate the body and has some safety risk.…”
mentioning
confidence: 99%
“…77 Several adverse events have been reported with the use of imiquimod, including pigmentary changes, superficial scarring, alopecia, 78 and rare induction of other dermatologic disorders such as pemphigus foliaceus, 79,80 aphthous ulcers, 81 vitiligo, 82-84 angioedema, 85 and eruptive epidermoid cysts. 86 Reports of induction of psoriasis associated with imiquimod have also been made.…”
Section: Basal Cell Carcinomamentioning
confidence: 99%